(untitled) (Acta Polytechnica CTU Proceedings, 2018)
Procedure of criticality calculations and uncertainty evaluations currently has several insufficiencies which could lead to potential non–conservativeness. Paper discuss and describes possibilities of elimination of these insufficiencies and thereby ensuring safely sub–critical results of calculations. Selection of experiments for validation based on similarity coefficients between systems acquired from TSUNAMI-IP is used for this purpose. TSUNAMI-IP operates with sensitivity of multiplication factor to cross sections of individual isotopes and reactions between compared systems. Moreover, TSUNAMI-IP determines uncertainty of calculations brought in using insufficiently similar experiments. Within research, effects of variable parameters used in calculations inputs are investigated. In conclusion optimized suggested approach for validations and uncertainty evaluation using TSUNAMI module from SCALE based on knowledge acquired within research is described.